N-(3-oxododecanoyl)-l-homoserine-lactone, a quorum sensing molecule, affects cellular content of nonprotein thiol content in rat lymphocytes: Its relation with intracellular Zn2+. (25th January 2018) - Nishimura-Danjobara, Yumiko; Oyama, Keisuke; Kanemaru, Kaori; Takahashi, Keiko; Yokoigawa, Kumio; Oyama, Yasuo
Abstract: Cellular actions of N-(3-oxododecanoyl)-l -homoserine-lactone (ODHL), a quorum sensing molecule of bacteria, were studied on rat thymocytes using a flow cytometer with appropriate fluorescent dyes to elucidate the effects of ODHL on host cells. A bell-shaped concentration-response relation was observed in the ODHL-induced changes in cellular glutathione content ([GSH]i). ODHL concentration-dependently increased intracellular Zn 2+ levels ([Zn 2+ ]i) and cellular O2 − content ([O2 − ]i). The bell-shaped relation induced by ODHL can be explained as follows: a low concentration of ODHL is expected to induce moderate oxidative stress that intracellularly releases Zn 2+ by converting thiols to disulfides. A slight elevation of [Zn 2+ ]i may increase the [GSH]i. On the other hand, it is likely that a high concentration of ODHL causes severe oxidative stress that further causes both the decrease in [GSH]i and the increase in [Zn 2+ ]i. Excessive increase in [Zn 2+ ]i may augment oxidative stress that further decreases the [GSH]i. Other notable actions induced by ODHL included the elevation of [Zn 2+ ]i by Zn 2+ influx and the increase in [GSH]i under Zn 2+ -free conditions. Therefore, it is suggested that ODHL elicits diverse actions on host cells. Highlights: N-(3-oxododecanoyl)-l -homoserine-lactone (ODHL) is a quorum sensing molecule. ODHL induced a 'bell-shaped' change in the glutathione content of rat thymocytes. ODHL concentration-dependently elevated intracellular Zn 2+ levels. ODHL increased cellular O2 − content in a concentration-dependent manner. ODHL may exhibit diverse actions on host cells.